As personagens femininas leitoras nos contos machadianos - Sanfelice, Simone Antonia (2014)
This research aims to investigate the presence of female reader characters within Machado de Assis tales narrative discourse, subject of very few critical studies. The corpus selected took into consideration the books read by the female reader characters and the interference of these readings in the narrative context. Through a detailed analysis based on 2008 Nova Aguilar Complete Works, we came to a selection of five tales, situated strategically on different phases of the author´s literary production: "O anjo das donzelas , Miss Dollar , D. Benedita , Capítulo dos chapéus and Missa do galo . We inquired in what way these female characters read and the extent in which the readings interfered their worldview. The hypothesis pointed different perspectives taken by the narrator in his ambivalent attitude of critical confirmation and denial, through irony, of the female reader characters pattern of reading. The theoretical references in this study were Wolfgang Iser and Wayne Booth, linked to the interaction between text and reader and to the discursive strategies of the author and the narrator in the story. The conclusion is that by means of gaps, potencies of denial and reversals in the narrative discourse, one can assure the way Machado de Assis projects to the actual reader, other interpretative possibilities. This contributes not only to a new female reader education, with critical capacity, but also to a woman with greater thinking and action autonomy, by the turn of the XIX to XX century, in Brazil